Adoptive Youth Ministry of Chap Clark. A Critical Appraisal from a Catholic Perspective - Jason Pinto (The Francis de Sales Scientific Society (TNFS.PL), 2024)
Based on the two fundamentals in Youth Ministry, namely the role of the youth in Youth Ministry as protagonists and subjects, as proposed in Christus Vivit, the apostolic exhortation on the Youth, a fresh thinking has been taking place in the Church. This study explores Youth Ministry based on the theology of Adoption propounded by Chap Clark, a Presbyterian Pastor from the United States, who has been in the field of Youth Ministry for the past 27 years. He proposes a Christian spirituality which is found in one's belongingness to a community, which he terms as "Adoptive Youth Ministry." The objective of Youth Ministry as adoption is for every child, every adolescent, and every young adult, to be so embraced by the community of faith that they are assured a home, a people, and a place where they can discover who they are and how they are able to contribute. It proposes a concrete step towards a process of integrating the youth in ecclesial life. A Catholic perspective on his method is an enrichment in the Church's theology of Youth Ministry.